Fostering Spiritual Intelligence in the Young Generation Through the PKN Course - Oktariani, Dini; Herlissha, Novita (CV. Rayyan Dwi Bharata, 2024)
Fostering Spiritual Intelligence in the Young Generation through Civics Courses The future of a nation today is in the hands of the younger generation, where the successors of the nation who are intelligent and have good morals and personality, can be realized through civic education. Considering that youth are agents of change who are always favored because they have high enthusiasm, creativity, competitiveness, and idealism. The younger generation must focus on aspects of instilling attitudes and personalities, in order to become good citizens, in addition to having intellectual intelligence, the younger generation must also have spiritual intelligence, because spiritual intelligence is an important thing for students. With spiritual intelligence will create a young generation who are moral and can change the world for the better. The population of this study is the entire young generation who are students from several universities and the younger generation who have worked and are domiciled in the Pangkalpinang City area with Purposive sampling involving 118 respondents who have characteristics aged 18-35 years who are domiciled in Pangkalpinang. The analysis method to be used to analyze the data is SPSS 26.0.